Persepsi Petani Terhadap Alih Fungsi Lahan di Subak Lanyahan, Kawasan Kecamatan Sawan, Kabupaten Buleleng, Provinsi Bali - ARSAYANA, I KETUT YUDI; WIDHIANTINI, WIDHIANTINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Farmers' Perception of Land Conversion in Subak Lanyahan, Sawan District, Buleleng Regency.  The success of food security programs heavily depends on the availability of agricultural land that allows farming activities to produce the required food for humanity. However, there are limitations to the available land, and it continues to diminish. The agricultural sector in Bali has long relied on a traditional institution that governs the irrigation and management of rice fields, known as Subak. Subak is a traditional organization deeply integrated with the socio-cultural aspects of the local community and globally recognized as a UNESCO World Cultural Heritage. This grants Subak significant importance within Bali's agricultural sector. While this recognition is a source of pride for Indonesia, especially Bali, it also presents a significant challenge in preserving the existence of Subak in Bali. This research focuses on understanding farmers' perceptions in terms of technical, economic, social, and cultural aspects. The study was conducted in Subak Lanyahan, Sawan District, Buleleng Regency, with a sample population of 49 respondents based on the application of the Slovin formula. Qualitative and quantitative descriptive analyses were used. The research findings indicate that farmers disagree with land conversion, encompassing technical, economic, social, and cultural aspects. From a technical perspective, farmers feel that the maintenance of Subak facilities is still adequate, irrigation systems function effectively, and they possess satisfactory agricultural equipment. In terms of economics, farmers believe they earn sufficient income. Moreover, from a social and cultural standpoint, farmers still have an interest and desire to continue working as farmers. This study offers recommendations to farmers to carefully consider their decisions regarding land conversion in the Subak Lanyahan area, Sawan District, Buleleng Regency. It is hoped that the research findings will contribute valuable insights for farmers, communities, and relevant stakeholders.